Investigation of hydrogen isotopes interaction with lithium CPS under reactor irradiation; Fusion Engineering and Design; Vol. 124 - Kulsartov T. V. Timur Valikhanovich; Tazhibaeva I. L. Irina Lashkarovna; Ponkratov Yu. V. Yury Valentinovich; Gordienko Yu. N. Yury Nikolaevich; Zaurbekova Zh. A. Zhanna Askhatovna; Baklanov V. V. Viktor Vladimirovich; Chikhray Ye.; Skakov M. K. Mazhyn Kanapinovich; Koyanbayev Ye.; Korovikov A. G. Aleksandr Genadvich; Nesterov E. A. Evgeny Alexandrovich (2017, 2017)
Title screen